Analisis persebaran mahasiswa teknik arsitektur pada lantai 4 gedung B.J. Habibie UIN Malang dengan pendekatan space syntax - Hadad, Fauzan Habib Al (Maliki Interdisciplinary Journal, 2024)
The B.J. Building Habibie is one of the lecture support buildings at UIN Maulana Malik Ibrahim Malang. This building is the basis for lectures in the science and technology cluster which is divided into 7 study programs and spread over 4 floors of the building. This study aims to analyze the distribution of Architectural Engineering students on the 4th floor of the B.J. Building. Habibie at UIN Malang used the Space Syntax approach. This research method involves the stages of data collection, descriptive analysis, and spatial analysis using special software for Space Syntax. Data regarding the number of students, space distribution, and physical characteristics of the 4th floor of the B.J. Building. Habibie was collected through surveys and direct observation. Furthermore, the data was analyzed using space syntax techniques to measure spatial density, connectivity, and integration of the 4th floor of the B.J. Building. Habibie. The results of this study are expected to provide a better understanding of how the physical space of the B.J. Habibie influenced the distribution of Architectural Engineering students on the 4th floor. This research makes an important contribution to the study of the effect of physical space on human behavior and interaction. It is hoped that the results of this research can become the basis for improving the design of spaces in similar buildings in the future, with the aim of improving the quality of user experience and facilitating better social interactions in the campus environment.